Laboratory Observations of Swash Signatures Using Video Imagery - Haoye Yang; Chi Zhang; Jian Shi; Xiangming Cao; Yuan Li (Journal of Marine Science and Engineering, 2022)
Swash motions are important for the design and assessment of beach protection projects, while the limitation of insightful observations in the swash zone still exists. An automatic identification method based on video imagery is developed to monitor and extract instantaneous swash motions in the laboratory. The method increases video sampling frequency and improves image enhancement in identification. The improved method fits well with the results of the manual method. The incident band roll-off of the swash spectrum in the experiment is consistent with those observed on natural beaches. Results have shown that on the barred beach, water depths influence the peak frequency in the incident band and cause a multi-peak swash spectrum. A large incident wave period causes a low peak frequency but high peak energy in the swash spectrum. Large incident wave height results in wider energy coupling, making swash to be saturated and more energy in swash energy. The existence of a barred beach promotes swash energy transferring from a high frequency to a low frequency.